2017
DOI: 10.11646/zootaxa.4226.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Species of the genus Euseius Wainstein (Acari: Phytoseiidae: Amblyseiinae) from Taiwan

Abstract: The six mite species of the genus Euseius Wainstein from Taiwan are reviewed, including E. ovalis (Evans), E. daluensis sp. nov., E. macaranga sp. nov., E. paraovalis sp. nov., and two species recorded for the first time in Taiwan, E. aizawai (Ehara & Bhandhufalck) and E. circellatus (Wu & Li). Measurements of these species and an identification key for adult females of the six Euseius species from Taiwan are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Among them, E. gallicus Kreiter & Tixier has been used commercially for whiteflies and thrips control (Biobest, 2018). In a decade-long survey conducted by the authors of the present study, six species-E. aizawai (Ehara & Bhandhufalck), E. circellatus (Wu & Li), E. daluensis Liao & Ho, E. macaranga Liao & Ho, E. ovalis (Evans), and E. paraovalis Liao & Ho-were found in Taiwan (Liao et al 2017a). visible on the dorsal shield.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Among them, E. gallicus Kreiter & Tixier has been used commercially for whiteflies and thrips control (Biobest, 2018). In a decade-long survey conducted by the authors of the present study, six species-E. aizawai (Ehara & Bhandhufalck), E. circellatus (Wu & Li), E. daluensis Liao & Ho, E. macaranga Liao & Ho, E. ovalis (Evans), and E. paraovalis Liao & Ho-were found in Taiwan (Liao et al 2017a). visible on the dorsal shield.…”
Section: Introductionmentioning
confidence: 62%
“…However, only two specimens have been found in Southern Taiwan and the biological control potential of this species needs further investigations. Liao et al (2017a) reported that Taiwanese E. aizawai specimens had two morphological types on the dorsal shield (e.g. anterolateral dorsal shield reticulated and entire dorsal shield reticulated).…”
Section: Female (N=3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Amblyseiinae is the largest subfamily in the family Phytoseiidae, with 1816 nominal species in the world, included in 66 genera (Demite et al 2019). So far 196 species belonging to 15 genera of phytoseiid mites have been recorded in China (Wu et al 2009;Fang et al 2017;Liao et al 2017Liao et al , 2018Demite et al 2019).…”
Section: Introductionmentioning
confidence: 99%